Use of the Delphi process in paediatric cataract management. Issue 5 (29th September 2015) - Serafino, Massimiliano; Trivedi, Rupal H; Levin, Alex V; Wilson, M Edward; Nucci, Paolo; Lambert, Scott R; Nischal, Ken K; Plager, David A; Bremond-Gignac, Dominique; Kekunnaya, Ramesh; Nishina, Sachiko; Tehrani, Nasrin N; et al.
Abstract : Purpose: To identify areas of consensus and disagreement in the management of paediatric cataract using a modified Delphi approach among individuals recognised for publishing in this field. Design: A modified Delphi method. Participants: International paediatric cataract experts with a publishing record in paediatric cataract management. Methods: The process consisted of three rounds of anonymous electronic questionnaires followed by a face-to-face meeting, followed by a fourth anonymous electronic questionnaire. The executive committee created questions to be used for the electronic questionnaires. Questions were designed to have unit-based, multiple choice or true–false answers. The questionnaire included issues related to the preoperative, intraoperative and postoperative management of paediatric cataract. Main outcome measure: Consensus based on 85% of panellists being in agreement for electronic questionnaires or 80% for the face-to-face meeting, and near consensus based on 70%. Results: Sixteen of 22 invited paediatric cataract surgeons agreed to participate. We arrived at consensus or near consensus for 85/108 (78.7%) questions and non-consensus for the remaining 23 (21.3%) questions. Conclusions: Those questions where consensus was not reached highlight areas of either poor evidence or contradicting evidence, and may help investigators identify possible research questions.